Penggunaan Material Bambu sebagai Bahan Utama Konstruksi pada Bangunan Green Village Bali - Bella Pertiwi; Maulia Atul I’annah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Bamboo is one of the fastest growing plants in the world. One of them is that in Indonesia, bamboo plants grow well and are spread very widely. Bamboo’s rapid growth makes it easy to find and a sustainable source of material. Bamboo is a strong and light material so it is suitable for use as a building material. One of them is the Green Village Bali building which is one of the famous sustainable architectural projects in Indonesia. Green Village Bali uses bamboo as the main construction material because of its flexibility, strength, good durability and fast growing properties. The use of bamboo material in Green Village Bali is not only due to its abundant availability but also its natural aesthetic that blends with nature, supporting environmentally friendly and sustainable principles, thereby creating architecture that is unique and harmonious with nature. This study discusses the structural advantages of bamboo, as well as the challenges faced, such as treatment for weather and insect resistance, as well as the preservation process which requires special technology so that bamboo is durable an:d suitable for long-term use. The study results show that bamboo as a construction material for Green Village Bali is not only able to provide natural aesthetics and good functionality to buildings, but also contributes significantly to reducing the carbon footprint. In addition, the application of bamboo increases public awareness of the importance of natural and sustainable building materials to support more environmentally friendly development in the future.